N-Vivo Analysis on Indonesia Islamic Insurance Studies - Maliha, Hasna (SMART Insight, 2023)
This study seeks to map research related to Islamic insurance in Indonesia published by Dimensions indexed journals from 2006 to 2023. NVivo 12 Plus was used to conduct a thematic review and frequency was used to evaluate 207 publications in the scientific literature. The results found that the number of publications fluctuates from year to year related to Islamic insurance research in Indonesia, indicating that this topic is an interesting topic and must continue to be developed. In addition, various foci of discussion and cluster analysis that describe the research path in Islamic insurance research in Indonesia include Efficiency and Islamic Insurance in Indonesia, Policy and Islamic Insurance in Indonesia, Banking and Islamic Insurance in Indonesia, and Company and Islamic Insurance in Indonesia. This research can be used as a starting point for experts to build graphic visualizations of Islamic insurance research patterns in Indonesia in published scientific research.